EVALUASI PROGRAM KELUARGA HARAPAN (PKH) (Studi Kasus Di Desa Tondong Belang Kecamatan Mbeliling Kabupaten Manggarai Barat) - Maria februana Defitri; Alfred Omri Ena Mau; Wiliam Djani (PT. Hasba Edukasi Mandiri, 2025)
The Family Hope Program (PKH) aims to provide cash assistance to Very Poor Households (RTSM) to improve the quality of Human Resources (HR) in education, health, and social welfare. However, in Tondong Belang Village there are problems in the distribution of assistance that is not on target and inappropriate utilization. This study aims to analyze the achievement of the PKH implementation process in Tondong Belang Village, Mbeliling Sub-district,West Manggarai Regency, using descriptive methods and a qualitative approach. Based on William N. Dunn's policy evaluation theory, six evaluation criteria were analyzed: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Data were collected through observation, interviews, and documentation. The results show that the implementation of PKH since 2015 has had a positive impact, although there are still challenges that need to be overcome to improve the effectiveness of the program in the future.